Black bone : 25 years of the Affrilachian poets - Spriggs, Bianca Lynne (The University Press of Kentucky, 2017)
The Appalachian region stretches from Mississippi to New York, encompassing rural areas as well as cities from Birmingham to Pittsburgh. Though Appalachia's people are as diverse as its terrain, few other regions in America are as burdened with stereotypes. Author Frank X Walker coined the term "Affrilachia" to give identity and voice to people of African descent from this region and to highlight Appalachia's multicultural identity. This act inspired a group of gifted artists, the Affrilachian Poets, to begin working together and using their writing to defy persistent stereotypes of Appalachia as a racially and culturally homogenized region. After years of growth, honors, and accomplishments, the group is acknowledging its silver anniversary with Black Bone. Edited by two newer members of the Affrilachian Poets, Bianca Lynne Spriggs and Jeremy Paden, Black Bone is a beautiful collection of both new and classic work and features submissions from Frank X Walker, Nikky Finney, Gerald Coleman, Crystal Wilkinson, Kelly Norman Ellis, and many others. This illuminating and powerful collection is a testament to a groundbreaking group and its enduring legacy.